Two antagonistic response regulators control Pseudomonas aeruginosa polarization during mechanotaxis. (16th February 2023) - Kühn, Marco J; Macmillan, Henriette; Talà, Lorenzo; Inclan, Yuki; Patino, Ramiro; Pierrat, Xavier; Al‐Mayyah, Zainebe; Engel, Joanne N; Persat, Alexandre
Abstract: The opportunistic pathogen Pseudomonas aeruginosa adapts to solid surfaces to enhance virulence and infect its host. Type IV pili (T4P), long and thin filaments that power surface‐specific twitching motility, allow single cells to sense surfaces and control their direction of movement. T4P distribution is polarized to the sensing pole by the chemotaxis‐like Chp system via a local positive feedback loop. However, how the initial spatially resolved mechanical signal is translated into T4P polarity is incompletely understood. Here, we demonstrate that the two Chp response regulators PilG and PilH enable dynamic cell polarization by antagonistically regulating T4P extension. By precisely quantifying the localization of fluorescent protein fusions, we show that phosphorylation of PilG by the histidine kinase ChpA controls PilG polarization. Although PilH is not strictly required for twitching reversals, it becomes activated upon phosphorylation and breaks the local positive feedback mechanism established by PilG, allowing forward‐twitching cells to reverse. Chp thus uses a main output response regulator, PilG, to resolve mechanical signals in space and employs a second regulator, PilH, to break and respond when the signal changes. By identifying the molecular functions of two response regulators that dynamically control cell polarization, our work provides a rationale for the diversity of architectures often found in non‐canonical chemotaxis systems. Synopsis: Pseudomonas aeruginosa switches the polarity of type IV pili (T4P) to guide itself on solid surfaces. This study shows that the chemotaxis‐like sensing system Chp decodes and transmits the mechanical signals to regulate the localization and activity of two antagonistic response regulators. Chp promotes local T4P assembly through asymmetric localization and activation of the response regulator PilG. The histidine kinase ChpA recruits and activates PilG by phosphotransfer. The response regulator PilH antagonizes PilG, leading to the inversion of T4P polarity. PilH inhibits the phosphorylation of PilG to break a local positive feedback loop, enabling forward‐twitching cells to reverse. Abstract : The chemotaxis‐like sensing system Chp localizes and activates the type IV pili extension regulators PilG and PilH to determine the direction of Pseudomonas motility.